Improving Okra Production by Poultry Manure Application in Highland Acid Oxisols of Dschang, Western Cameroon - Tamfuh, Primus Azinwi; Epie, Isaac Mpako; Ndzana, Georges Martial; Tchinda, Romary Ngnipa; Ibrahim, Achille Bienvenu; Nongha, Laura Ingrid Nfota; Kabeyene, Veronique Beyala Kamgang (Asian Soil Research Journal, 2024)
Problem Statement: Low yields of crops in Sub-saharan Africa are often associated with low soil fertility. However, due to high cost and negative environmental impact of chemical fertilizers, using cheap and readily available organic manures such as poultry manure (PM) has become indispensable. Aim: To evaluate the effect of different rates of PM on soil fertility and the performance of Okra (Abelmoschus esculentus) in the Cameroon Western Highlands. Methodology: The study was carried out in the field and in the laboratory. The experimental plot (191.25 m2) in the field was designed in a randomized complete block design with six treatments and three replications: 0 t ha-1 of PM (To), 3 t ha-1 of PM (T1), 6 t ha-1 of PM (T2), 9 t ha-1 of PM (T3), 12 t ha-1 of PM (T4), and 250 kg of NPK 12-14-19 (T5). Soil samples were analyzed in the laboratory by standard procedures before and after treatment. Results: Treatment T0 had a clay loam texture, acidic pH (5.4), relatively high organic carbon content (1.92%), moderate total nitrogen (0.33%) and moderate available phosphorus (36.07 mg  kg-1). The exchangeable complex revealed high K+ (1.02 cmol kg-1), low Ca2+ (2.60 cmol kg-1) and Mg2+ (1.04 cmol kg-1), average Na+ (0.33 cmol kg-1). After treatment, soil pHH2O, available phosphorus and exchangeable K, Ca, and Mg increased after harvest whereas Na decreased for all the treatments.  The effect of the treatments on growth parameters was such that T3>T4>T1>T5>T2>T0. The global trend of yield parameters was such that T3>T4>T5>T1>T0>T2. Economically, treatments T3, T4, and T5 were profitable and recommendable for popularization, with a benefit-to-cost-ratio (BCR) >2. The most economically viable treatment was T3 with a profit rate (PR) of 601.66% and a BCR value of 7.02, while T2 was the least economically viable treatment with a negative PR of -32.14% and a BCR of -33.67. Conclusion: Farmers in Western highlands can produce okra profitably and sustainably using PM at a rate of 9 tha-1f.